INFLUENCE OF CIGARETTE SMOKING DURATION ON ENDOTHELIAL CELL FUNCTION Tatyana M. Popova1, Tatyana V. Gorbach1, Tatyana I. Tsygankova2, Natalia O. Shushliapina1 Department of Biochemistry, Kharkiv National Medical University, Kharkiv, Ukraine Outpatient Dep - Popova, Tatyana Mikhailovna; Gorbach, Tatyana Viktorovna; Tsygankova, Tatyana Ivanovna; Shushliapina, Natalia Olegovna (Medicinski časopis, 2018)
Objective. Smoking is important cardiovascular risk factor to which duration and amount of daily cigarettes consumption contributes. The aim of our research was to evaluate the influence of the cigarette smoking duration on the nitrate, nitrite, S-nitrosothiols and endothelin-1 levels in saliva of smokers. Methods. Four groups of 60 subjects were recruited: non-smoking subjects (control group, n=15); smoking subjects have smoked for two years (group I, n=15); smoking subjects have smoked for four years (group II, n=15); and smoking subjects have smoked for six years (group III, n=15). The blood pressure, weight and height of all subjects were measured. Body mass index was calculated. Determination of nitrate, nitrite, S-nitrosothiols and endothelin-1 was done in each salivary sample collected from 60 subjects. Results. The results of our study showed that the systolic blood pressure and diastolic blood pressure did not differ between the control group and group I. However, the systolic blood pressure as well as diastolic blood pressure were significantly greater in group II and group III subjects as compared to controls. Smokers and non-smokers had normal body mass index vales. The levels of salivary nitrate, nitrite and S-nitrosothiols were significantly lower in smokers of group II and group III than in control subjects. Salivary endothelin-1 concentrations were significantly higher in subjects of group II and group III than controls. Conclusion. In this study the substantial differences between smokers and non-smokers in levels of stable metabolites of NO and endothelin-1 are due to the causal effects of smoking.